Explaining Novice Nurses’ Experience of Weak Professional Confidence: A Qualitative Study - Bahareh Najafi BScN, MScN, PhD; Ahmad Nasiri BScN, MScN, PhD (SAGE Open Nursing, 2023)
Introduction The majority of newly graduated nurses are not prepared to work at the bedside; therefore, they may not have the appropriate self-confidence. Objective(s) The present qualitative study aimed to explain the novice nurses’ experience of weak professional confidence. Design This qualitative study was performed using a content analysis method. Methods Content analysis was utilized to identify themes from interview transcripts. They were included in the study by purposeful sampling. Participants were interviewed through face-to-face and unstructured interviews. All data were recorded, transcribed, and analyzed based on the Graneheim and Lundman method. Results Thirteen nurses participated in interviews. After data collection, all interviews were implemented and reviewed and the categories and subcategories were extracted. Three main categories containing turbulence in working life, unpleasant interactions, and lack of knowledge were extracted. Conclusion According to the study findings, most novice nurses experienced turbulence in their working life, unpleasant interactions, and a lack of knowledge that affected their self-confidence. Therefore, educational and support programs are suggested to improve novice nurses’ professional confidence. Relevance to Clinical Practice According to the results of the study, the lack of self-confidence in novice nurses reduces the quality of care. Therefore, taking into account the experiences of the participants, nursing education managers should plan in such a way as to improve the self-confidence of the graduates. In addition, novice nurses need to be supported by their managers and colleagues to develop their professional confidence to provide more effective care.